2022
DOI: 10.15832/ankutbd.990781
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antibiotic resistance profiles of Lactococcus garivieae isolated from rainbow trout (Oncorhynchus mykiss) farms in Muğla, Turkey

Abstract: This study was aimed to determine the current antibiotic resistance of Lactococcus garvieae, which causes significant economic losses in rainbow trout (Oncorhynchus mykiss) farms. For the study, three farms located around a stream were visited in two consecutive disease outbreaks. Bacteria were isolated from the diseased fish and all bacterial isolates were identified using conventional and molecular methods. Then, they were examined for 5 different antibiotic resistance genes and their antibiotic susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Our results for Thai isolates of L. garvieae that were resistant to norfloxacin, oxolinic acid, and flumequine but highly susceptible to ampicillin and amoxicillin agreed with results for Rainbow Trout L. garvieae isolates from Turkey (Sezgin et al. 2023). Differences in the degree of susceptibility of L. garvieae to enrofloxacin, sulfamethoxazole/trimethoprim, oxytetracycline, ampicillin, and flumequine have been reported in Rainbow Trout from diverse geographic origins (Chang et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results for Thai isolates of L. garvieae that were resistant to norfloxacin, oxolinic acid, and flumequine but highly susceptible to ampicillin and amoxicillin agreed with results for Rainbow Trout L. garvieae isolates from Turkey (Sezgin et al. 2023). Differences in the degree of susceptibility of L. garvieae to enrofloxacin, sulfamethoxazole/trimethoprim, oxytetracycline, ampicillin, and flumequine have been reported in Rainbow Trout from diverse geographic origins (Chang et al.…”
Section: Discussionsupporting
confidence: 90%
“…The L. garvieae and S. agalactiae isolates from this study showed either resistance or developing resistance to quinolones, including norfloxacin, oxolinic acid, flumequine, and enrofloxacin, while revealing susceptibility to other antimicrobial classes, such as βlactams, tetracyclines, and folate pathway antagonists. Our results for Thai isolates of L. garvieae that were resistant to norfloxacin, oxolinic acid, and flumequine but highly susceptible to ampicillin and amoxicillin agreed with results for Rainbow Trout L. garvieae isolates from Turkey (Sezgin et al 2023). Differences in the degree of susceptibility of L. garvieae to enrofloxacin, sulfamethoxazole/trimethoprim, oxytetracycline, ampicillin, and flumequine have been reported in Rainbow Trout from diverse geographic origins (Chang et al 2002;Didinen et al 2014;Balta and Balta 2019;Karami et al 2019).…”
Section: Discussionsupporting
confidence: 86%
“…The methodology employed in tests for antibiotic susceptibility can have an impact on the outcomes ( Sezgin et al, 2023 ). In accordance with the most recent CLSI recommendations ( CLSI, 2021 ), we employed 5% sheep blood-added MHA (SB-MHA) to assess the antibiotic susceptibility of the microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…A digital caliper was used to measure the diameter of the inhibition zones that formed around the antibiotic discs at the end of the incubation period. Based on this measurement and related references ( Sezgin et al, 2023 ), the isolates were categorized as susceptible, moderately susceptible, and resistant.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of L. garvieae infection in the human literature has included the use of ceftazidime or other third-generation cephalosporins including ceftriaxone; however, recent antimicrobial susceptibility tests have not included ceftazidime among the other cephalosporins tested. 3,8,22,24 Given the zoonotic concerns surrounding L. garvieae and the popularity of bearded dragons as pets, the isolation of this pathogen from the species is important. Future studies to determine the prevalence, ecology, and epidemiology of L. garvieae in the reptile pet trade are indicated.…”
mentioning
confidence: 99%